2014
DOI: 10.1039/c4ra03935a
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based thermoset composites from epoxidised linseed oil and expanded starch

Abstract: a Bio-based thermoset composites comprising epoxidised linseed oil (ELO), a bio-derived diacid crosslinker (Pripol 1009) and starch are reported. High amylose corn starch in its native, gelatinised and retrograded forms were used in the formulation to yield water resistant films with good thermal stability. The textural properties of gelatinised and retrograded starches were characterised using scanning electron microscopy and porosimetry and their thermal stability was determined using thermogravimetric analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 59 publications
0
36
0
1
Order By: Relevance
“…28 Based on previous studies, [29][30][31][32] the possible interactions between ELO, DCAs and DMAP are proposed as shown in Scheme 1. 28 Based on previous studies, [29][30][31][32] the possible interactions between ELO, DCAs and DMAP are proposed as shown in Scheme 1.…”
Section: Ft-ir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…28 Based on previous studies, [29][30][31][32] the possible interactions between ELO, DCAs and DMAP are proposed as shown in Scheme 1. 28 Based on previous studies, [29][30][31][32] the possible interactions between ELO, DCAs and DMAP are proposed as shown in Scheme 1.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…Vilela et al 44 studied the thermal stability of polyesters prepared from C 26 dicarboxylic acid with different chain length of diols (C 4 , C 12 , C 26 ) and their study confirmed that better thermal stability was obtained with higher chain length of polyesters. 29,46 While the second stage beyond 430 o C resulted from the ester groups formed by the ring-opening reactions between DCAs and epoxy groups. 7 (a) clearly shows that the resins experienced a twostage decomposition process in N 2 .…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…More recently, in 2014, Supanchaiyamat et al reported using epoxidised linseed oil and expanded starch (from the aforementioned Starbon Âź process) to produce a fully bio-based composite with 227% improvement in tensile strength and 166% enhancement in Young’s modulus, compared to those with no added starch, suggesting it as a replacement for vinyl based films [249]. …”
Section: Lipidsmentioning
confidence: 99%
“…Therefore, many works have been focused on the valorization of renewable resources towards epoxy resins to restrict the use of DGEBA . Numerous alternative precursors for DGEBA‐free resins have been described, such as terpenes, linseed oil derivatives, sucrose soyate, and rosin acid oligomers . Research on isosorbide‐based epoxy compounds also revealed good mechanical properties of the resulting cured materials and led to the commercialization of the diglycidyl ether of isosorbide .…”
Section: Introductionmentioning
confidence: 99%